DIAGNOSIS OF MYCOBACTERIUM TUBERCULOSIS BY ELISA AND REAL TIME PCR - MAYS NOORI FALIH (International Journal of Pharma and Bio Sciences, 2013)
Until now there has been little effort to improve techniques for diagnosing tuberculosis hence control of tuberculosis is hampered by slow, insensitive diagnostic methods. The effective treatment of tuberculosis will be one of the greatest public health interventions. In this study we assessed the performance of Real Time PCR and ELISA. IgG antibodies to MTb are investigated by ELISA in chronic infections. Also, M. tuberculosis DNA is extracted from samples and amplified using Real Time Amplification and detected using fluorescent reporter dye probes specific for M. tuberculosis. We found a 100% match of the results for MTB detection. Future research on this topic is certainly needed, and this research would be benefited from the increased detection capacities of both Real Time PCR and ELISA.